Investigation on structural, optical and electrical nature of pure and Cr-incorporated cobalt oxide nanoparticles prepared via co-precipitation method for photocatalytic activity of methylene blue dye - Reena, R. Sylvia; Aslinjensipriya, A.; Jose, M.; Das, S. Jerome (Journal of materials science. Materials in electronics, 2020)
Spinel-type cobalt oxide (Co 3 O 4 ) nanoparticles have been the subject of great deliberations for material scientists in the recent tenner, owing to their favorable and distinct combination of its thermal and optical properties. Cobalt oxide nanocrystalline powder was synthesized by a lucid co-precipitation technique maintained at low calcination temperature. Pure and different concentrations of chromium-doped cobalt oxide nanoparticles were synthesized by adding various concentrations of chromium nitrate to cobalt nitrate. The crystalline size of the as-synthesized sample was found to be decreasing on increasing the chromium concentration as dopants in ranging ratios outlined by powder X-ray diffraction and portraits the crystallographic pattern formed as a salient peak at (311). The stretching bands from the range 400–4000 cm −1 were substantiated from FTIR spectra confirming the spinel structure. Two broad absorbance peaks of energy bandgap were observed in Co 3 O 4 nanoparticles and optical bandgap was further estimated using Tauc & Davis–Mott relation. The high-resolution transmission electron microscope (HRTEM) image indicates the sphere-like morphology. The dielectric property of the samples was studied in the frequency at room temperature also the electronic properties like valence electron plasma energy, Penn gap, and Fermi energy was calculated the AC conductivity due to the narrow size distribution of grains was also displayed. The synthesized chromium-doped cobalt oxide was studied for its application in photocatalytic degradation of organic Methylene Blue (MB) dye under visible light illumination.